Periodontal and peri‐implant diseases in centenarians. (25th August 2020) - Sekundo, Caroline; Langowski, Eva; Kilian, Samuel; Frese, Cornelia
Abstract: Aims: To report the prevalence of periodontal and peri‐implant diseases in centenarians in South‐Western Germany, examine associations with sociodemographic factors and explore age‐related trends. Material and methods: Eligible persons born before 1920 were identified from population registries in South‐Western Germany. A total of 55 centenarians were visited at home or in nursing care facilities. Of them, 35 were dentate, 33 of which underwent periodontal examination. Implants in 2 edentulous patients were also registered. Results: The mean number of teeth was 9.5 ± 7.1; centenarians in need of nursing care had considerably less teeth than others (8.5 versus. 17.0 teeth, p = .03). Mean probing depth was 2.7 ± 0.8mm; mean clinical attachment loss was 4.2 ± 1.7 mm. Severe tooth mobility (degree 2 or 3) and furcation involvement were present in approximately 3% of eligible teeth. According to CDC/AAP classification, 25.8% of centenarians had no or mild periodontitis, 54.8% of centenarians had moderate periodontitis, and only 19.4% were severely affected. Of 27 implants examined in 5 centenarians, 59.3% were classified as healthy, 29.6% had peri‐implant mucositis, and 11.1% had peri‐implantitis. Conclusions: This study reveals the predominance of moderately severe disease in centenarians. While there were high levels of moderate periodontitis and peri‐implant mucositis, signs of severe periodontitis, severe furcation involvement, tooth mobility or peri‐implantitis were less frequent.